Kinerja Kelompok Tani dalam Pengelolaan Hutan Tanaman Rakyat di Desa Bacu-Bacu Kabupaten Barru - Ridwan Ridwan; Mas'ud Junus; M. Asar Said Mahbub; Restu Puput Windarti (Fakultas Kehutanan, Universitas Hasanuddin, 2018)
This study aims to describe the variables and indicators that affect the performance of farmer groups in forest management before and after the determination of HTR area and analyze the performance of farmer groups in forest management before and after the determination of Community Timber Plantation area. This research is done by the study of diagnostic study and interview then data analysis is done with quantitative and qualitative analysis. The results show that the performance of farmer groups is strongly influenced by group work plans, management areas, land preparation and breeding processes. The performance of farmer groups as a whole is good / not good because not yet the issue of IUPHHK-HTR SK individually by Padang Pobbo forest farmer group.